UK and Twenty Comparable Countries GDP-Expenditure-on-Health 1980-2013: The Historic and Continued Low Priority of UK Health-Related Expenditure - Andrew J.E. Harding; Colin Pritchard (Kerman University of Medical Sciences, 2016)
It is well-established that for a considerable period the United Kingdom has spent proportionally less of its gross domestic product (GDP) on health-related services than almost any other comparable country. Average European spending on health (as a % of GDP) in the period 1980 to 2013 has been 19% higher than the United Kingdom, indicating that comparable countries give far greater fiscal priority to its health services, irrespective of its actual fiscal value or configuration. While the UK National Health Service (NHS) is a comparatively lean healthcare system, it is often regarded to be at a 'crisis' point on account of low levels of funding. Indeed, many state that currently the NHS has a sizeable funding gap, in part due to its recently reduced GDP devoted to health but mainly the challenges around increases in longevity, expectation and new medical costs. The right level of health funding is a political value judgement. As the data in this paper outline, if the UK 'afforded' the same proportional level of funding as the mean averageEuropean country, total expenditure would currently increase by one-fifth.